Energy Dissipation and Damage Evolution Characteristics of Shale under Triaxial Cyclic Loading and Unloading - Ziyun Li; Song Xie; Qianghui Song; Peiyong Wang; Dongyan Liu; Baoyun Zhao; Wei Huang (Advances in Materials Science and Engineering)
Rock engineering is highly susceptible to cyclic loads resulting from shale gas exploitation; it is very important to study the failure mechanism of underground rock mass under cyclic load. To investigate the energy dissipation and damage evolution characteristics of shale under triaxial cyclic loading and unloading conditions, a series of triaxial incrementally cyclic loading and unloading tests under different confining pressures (10 MPa, 15 MPa, 20 MPa, and 30 MPa) were carried out. The variation of plastic strain of shale under four confining pressures was analyzed, and the evolution characteristics of dissipated energy and energy dissipation ratio were discussed. The results show that: the peak strength and peak strain of shale increase with the increase in confining pressures. Meanwhile, the plastic strain of rock under cyclic loading increases rapidly first, then develops steadily, and finally increases sharply with the increase in axial strain. The energy dissipation ratio-strain curve presents a spoon-shaped evolution feature, and can be divided into three stages: a linear decline stage, a steady development stage, and a rapid increase stage, respectively. However, the trend of elastic modulus of shale was opposite to that of the energy dissipation ratio. Accordingly, the energy dissipation ratio can be regarded as the damage factor to describe the degradation of shale. Based on the evolution of dissipated energy, a theoretical equation of shale stress-strain evolution was established. By substituting the test data into the formula, it is found that the calculated results are basically consistent with the test data, and the peak strains and peak stress calculated by the equation are in good agreement with the test data. The findings could provide important theoretical support for the energy dissipation and damage evolution analysis in the failure process of shale under cyclic stress conditions.